The influence of perinatal maternal exposure to dibutyl phthalate on glucolipid metabolism in adult female offspring. Issue 6 (November 2022) - Zhou, Kunyan; Cheng, Ran; Zhu, Mei; Yang, Meina; Shen, Xiaoyang; Luo, Xiaoyan; Ma, Li; Xu, Liangzhi; Zhang, Jing
Abstract: Background: Maternal exposure to dibutyl phthalate (DBP) may result in obesity in female offspring. However, the underlying mechanisms remain elusive. Materials and methods: Sprague-Dawley rats were intraperitoneally injected with different doses of DBP and corn oil from gestational day 7 until the end of lactation. The weights, visceral fat percentage, serum lipid, insulin and glucose, protein levels of PI3K signal pathway in muscle were detected in F1 female offspring. Results: Although the birth weight of F1 female offspring was not different among groups, the weights were heavier in DBP groups from postnatal day 7 to adult (P < 0.001). The visceral adipose percentage in adult female offspring was increased by perinatal exposure to DBP (P < 0.001). Decreased serum level of triglyceride (P = 0.001) in F1 female offspring was found in DBP group as compared to control, especially in medium and high DBP. However, none difference was found for fasting glucose, prolactin, HOMA-IR, fasting insulin, total cholesterol, adiponectin. Different protein levels of GPR30 were observed in muscle of female offspring among four groups (P = 0.016). The protein level of AKT seemed higher in DBP group but without statistical significance (P = 0.05). None difference was observed for the protein levels of PI3K, p-AKT, pAKT/AKT, PTEN, GLUT4, InsR, IRS. Conclusion: Maternal perinatal exposure to DBP might induce obesity and accumulation of visceral adipose tissue for the adult female offspring. Serum glucolipid and local signal transduction of PTEN/PI3K/AKT pathway in muscle were not adversely affected by perinatal exposure to DBP for adult female offspring.